Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study. Issue 11 (2nd November 2022) - Malvisi, Lucio; Yarraguntla, Aparna; Mortier, Marie-Cécile; Osman, Karen; Cleary, David W.; Sente, Béatrice; Pascal, Thierry G.; Weynants, Vincent; Clarke, Stuart C.; Taddei, Laura; Wilkinson, Tom M. A.; Devaster, Jeanne-Marie; et al.
Abstract: Background: Bacterial infections are associated with acute exacerbations of chronic obstructive pulmonary disease (AECOPD), but the mechanism is incompletely understood. Method: In a COPD observational study (NCT01360398), sputum samples were collected monthly at the stable state and exacerbation. Post-hoc analyses of 1307 non-typeable Haemophilus influenzae (NTHi) isolates from 20 patients and 756 Moraxella catarrhalis isolates from 38 patients in one year of follow-up were conducted by multilocus sequence typing (MLST). All isolates came from cultured sputum samples that were analyzed for bacterial species presence, apparition (infection not detected at the preceding visit), or acquisition (first-time infection), with the first study visit as a baseline. Strain apparition or new strain acquisition was analyzed by MLST. The odds ratio (OR) of experiencing an exacerbation vs. stable state was estimated by conditional logistic regression modelling, stratified by patient. Results: The culture results confirmed a significant association with exacerbation only for NTHi species presence (OR 2.28; 95% confidence interval [CI]: 1.12–4.64) and strain apparition (OR 2.38; 95% CI: 1.08–5.27). For M. catarrhalis, although confidence intervals overlapped, the association with exacerbation for first-time species acquisition (OR 5.99; 2.75–13.02) appeared stronger than species presence (OR 3.67; 2.10–6.40), new strain acquisition (OR 2.94; 1.43–6.04), species apparition (OR 4.18; 2.29–7.63), and strain apparition (OR 2.78; 1.42–5.42). This may suggest that previous M. catarrhalis colonization may modify the risk of exacerbation associated with M. catarrhalis infection. Conclusions: The results confirm that NTHi and M. catarrhalis infections are associated with AECOPD but suggest different dynamic mechanisms in triggering exacerbations.